2022
DOI: 10.1038/s41531-022-00376-x
|View full text |Cite
|
Sign up to set email alerts
|

A 6-month longitudinal study on worsening of Parkinson’s disease during the COVID-19 pandemic

Abstract: Further studies are required to investigate the impact of the COVID-19 pandemic on Parkinson’s disease (PD) progression. This study investigated the motor and non-motor progression of people with PD (PWP) at 6 months during the COVID-19 pandemic compared with that during the pre-pandemic period. Patients were recruited from Ain Shams University Hospitals, Cairo, in the period between April 2019 and December 2020. Fifty patients were included, of whom 17 and 33 patients were followed for 6 months before and dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
2
12
0
3
Order By: Relevance
“…Unfortunately, demographic data for the sample in that study were not provided, making it difficult to determine the reason for the lack of detectable motor impairment. In contrast, studies by Ineichen et al [32], Shalash et al [25], and Capecci et al [34], which had evaluation periods longer than six months, yielded results consistent with our findings. These studies reported an increase in the UPDRS Part III score during the lockdown period.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Unfortunately, demographic data for the sample in that study were not provided, making it difficult to determine the reason for the lack of detectable motor impairment. In contrast, studies by Ineichen et al [32], Shalash et al [25], and Capecci et al [34], which had evaluation periods longer than six months, yielded results consistent with our findings. These studies reported an increase in the UPDRS Part III score during the lockdown period.…”
Section: Discussionsupporting
confidence: 90%
“…However, it is noteworthy that 58.3% of the patients required medication adjustments for non-motor symptoms, indicating the importance of addressing these aspects during virtual consultations (Table 1). Previous studies, including Falla et al [24] and Shalash et al [25], have also reported a deterioration in the non-motor aspects of daily life, as measured by UPDRS Part I. It is important to note that these findings may vary across different populations and countries, reflecting the unique experiences and conditions of each study population during the pandemic.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The clinical deterioration was explained by the infection-related mechanisms and impaired pharmacokinetics of dopaminergic therapy (Cilia et al, 2020). Another retrospective study also reported a worsening of motor and non-motor symptoms with a significant increase in disease progression during the COVID-19 pandemic (Shalash et al, 2022).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have reported that COVID-19 not only aggravates motor and non-motor symptoms (Brown et al, 2020;D'Iorio et al, 2022) but also exacerbates the disease progression in PD patients (Shalash et al, 2022). Many of these studies have focused on the relationship between COVID-19 pandemic and clinical features of PD.…”
Section: Introductionmentioning
confidence: 99%